Planning for a Crisis, but Preparing for Every Day: What Predicts Schools' Preparedness to Respond to a School Safety Crisis? - Bradshaw, Catherine P.; Debnam, Katrina J.; Kush, Joseph M.; Lindstrom Johnson, Sarah (Frontiers in Communication, 2022)
This study aimed to identify potential gaps related to crisis preparedness at 98 public secondary schools, as such crises may occur following a substantiated eminent threat of school violence. Crisis preparedness data collected by trained external assessors captured knowledge of the procedure for responding in a safety-related crisis and process for notifying school staff, as well as the posting of the crisis plan in school locations. Data were analyzed in conjunction with data on student- and staff-reported school climate, school demographics, and external observations of the school. Analyses indicated that the staff were least aware of the process for notifying staff that a crisis was occurring. Middle schools, schools with higher levels of school disorder, and those with poorer reading and math scores were less likely to know the procedure, know the notification process, and have the plans posted in all locations. Schools also need to improve posting of school crisis procedures in shared and open spaces, such as the cafeteria and gymnasium; this is especially critical given that many school shootings occur in these large open spaces. Multilevel analyses indicated that staff perceptions of safety were significantly higher in schools in which the procedure was posted in all locations. Together, these findings provide evidence of a link among crisis planning, school context, and school climate, and complement the need for additional training on what to do following the substantiation of a credible and eminent threat.